An Ethnobiological Study of the Tamang People - Tamang, Ganesh (Our Nature, 2006)
Tamangs are one of the major ethnic groups of Nepal. Ethnobiological investigation of Tamang people of Gorsyang Village Development Committee of Nuwakot district was carried out. Information was documented from structured questionnaire and interviews with local people. They were found to have rich indigenous knowledge. They use different 12 animal names as calendar. A total of 11 animal species and 44 plant species were found to be used in medicinal purpose. Viscera of Hystrix brachyura, pancreas of fish and flesh of Rana tigrinai were found using in the treatment of asthma, jaundice and pneumonia. The fur of Lepus nigricollis is used to stop bleeding. Acorus calamus, Centilla asiatica and Terminalia chebula are the important medicinal plants, which they use to control throat, urine and gastric problems. The stem extract of Tinospora cordifolia is used in menstruation problems. Keywords: Ethnobiology, Tamang people doi:10.3126/on.v1i1.303 Our Nature (2003) 1: 37-41